Pengalaman Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa tentang Self Care, Adaptasi Diet dan Cairan - Hasan Hasan; Mulyati Mulyati; Dedi Supriadi; Iin Inayah; Susilawati Susilawati (Jurnal Keperawatan Silampari, 2022)
This study aims to find meaning from the experience of chronic kidney disease patients undergoing hemodialysis regarding their diet and fluid regimen so that a design for education is formed. The research method used is a qualitative research method with a phenomenological approach. The results of the study identified seven themes, namely; 1) Changes in the patient's physiological condition; 2) Expression of feelings about changes in health conditions; 3) Needs for support; 4) Changes in fulfilling dietary needs; 5) Changes in fulfilling fluid needs; 6) Needs to obtain information about treatment; 7) Barriers in following diet and fluids. In conclusion, this study recommends that patients increase their knowledge and information regarding adherence to diet and fluids. Keywords: Adaptation, Fluids, Diet, Hemodialysis Experience, Self Care